Wide-optical-band-gap transparent conductive copper chromate epitaxial film and preparation method thereof

Through the chemical solution deposition method, a wide optical bandgap transparent conductive copper chromate epitaxial film with excellent performance was successfully prepared, which solved the problems of complex preparation methods and high equipment cost in the prior art, and achieved low-cost and efficient film preparation and excellent performance.

CN119507020AInactive Publication Date: 2025-02-25ANQING NORMAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411690082.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to prepare high-quality wide optical bandgap transparent conductive copper chromate epitaxial films at low cost and efficiently, and the preparation method is complex and the equipment cost is high, which limits its application and promotion.

Method used

The copper chromate epitaxial film was prepared by spin coating, pyrolysis and annealing steps by chemical solution deposition, and the process parameters such as solution concentration, reaction temperature and time were adjusted to control the microstructure and performance of the film.

Benefits of technology

A wide optical bandgap transparent conductive copper chromate epitaxial film with excellent performance was successfully prepared, with low room temperature resistivity, high carrier mobility, high transmittance and low cost, which overcomes the problems of expensive equipment of traditional methods and harsh preparation conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507020A_ABST
    Figure CN119507020A_ABST
Patent Text Reader

Abstract

The invention discloses a wide-optical-band-gap transparent conductive copper chromate epitaxial thin film and a preparation method thereof.The preparation method of the thin film comprises the following steps that according to the stoichiometric ratio, copper nitrate and chromic nitrate are added into a mixed solvent of ethylene glycol and glacial acetic acid, and precursor colloid is obtained; al2O3 is used as a growth substrate, after cleaning, the precursor colloid forms a film on the surface of the growth substrate through a spin-coating method, and then an amorphous film is obtained through pyrolysis; and carrying out post-annealing treatment on the amorphous film in a reducing atmosphere to obtain the wide-optical-band-gap transparent conductive copper chromate (CuCrO2) epitaxial film. The wafer-level transparent conductive CuCrO2 epitaxial film with excellent performance is prepared in a non-vacuum environment, the operation process is simple, the requirement for expensive equipment is low, mass production is facilitated, and the method has good application prospects in the field of photoelectric devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of semiconductor technology, and in particular to a wide optical bandgap transparent conductive copper chromate epitaxial film and a preparation method thereof. Background Art

[0002] In the past few decades, the growing demand for transparent conducting oxides (TCOs) has driven the research on ultra-wide optical bandgap mercury-free materials with high conductivity, high energy efficiency and long lifetime. Wide optical bandgap transparent conductive films exhibit excellent conductivity and transparency in the ultraviolet (UV) region and can be applied in UV sensors, medical treatment, phototherapy and space exploration [1-2].

[0003] In recent years, copper chromate (CuCrO2) has shown very interesting optoelectronic properties, with an average visible transmittance between 40% and 60%, a band gap in the range of 2.9-3.1 eV, and a high carrier concentration (up to 10 22 cm -3 ), conductivity from 10 -4 to 10 2 S cm -1 , spanning several orders of magnitude [3-4]. At present, the main methods for growing CuCrO2 films at home and abroad are magnetron sputtering, molecular beam epitaxy, pulsed laser deposition, etc. Improving the electron mobility of CuCrO2 films is the core research direction to clarify its mechanism and application. However, the equipment and target materials used to prepare films by these methods are quite expensive, which seriously limits the application and promotion of CuCrO2 films as transparent conductive materials. In addition, the preparation of CuCrO2 films is mainly limited to the preparation of polycrystalline films. Polycrystalline films may be more prone to uneven crystallinity and crystal defects, resulting in poor electron mobility. It is still very important to develop low-cost and cost-effective CuCrO2 epitaxial film preparation methods [5].

[0004] Chemical solution deposition (CSD) is a method for preparing transparent conductive films in a non-vacuum environment and has been widely used in scientific research and industry. This film preparation technology can be carried out at room temperature and pressure, with low cost, and can obtain wafer-level functional films [6]. Since the experimental conditions for growing high-quality CuCrO2 films are quite harsh, and the preparation of CuCrO2 films is mainly limited to the preparation of polycrystalline films. At present, there are no reports on the successful preparation of transparent conductive CuCrO2 epitaxial films based on the solution method at home and abroad. Therefore, it is urgent to provide a new method for preparing CuCrO2 epitaxial films, so that the films not only have relatively low manufacturing costs, but also have low resistivity and high carrier mobility, and have high transmittance in the visible and near-infrared range.

[0005] [1]Yu X,Marks TJ,Facchetti A.Metal oxides for optoelectronic applications.Nat Mater.2016,15,4.

[0006] [2]Wang Z,Nayak PK,Caraveo-Frescas JA,et al.Recent developments in p-type oxide semiconductor materials and devices.Adv.Mater.2016,28,20.

[0007] [3]Jaewon Kim,Owen Kendall,Jiawen Ren,et al.Highly Conductive andVisibly Transparent p-Type CuCrO2 Films by Ultrasonic Spray Pyrolysis.ACSAppl.Mater.Interfaces 2022,14,9.

[0008] [4]Shengbin Nie,Ao Liu,You Meng,et al.Highly Conductive and VisiblyTransparent p-Type CuCrO2 Films by Ultrasonic Spray Pyrolysis.ACSAppl.Mater.Interfaces 2022,14,9.

[0009] [5]Tripurari S. Tripathi,Maarit Karppinen.Enhancedp-Type TransparentSemiconducting Characteristics forALD-Grown Mg-Substituted CuCrO2ThinFilms.Adv.Electron.Mater.2017,3,1600341.

[0010] [6]Renhuai Wei,Penglai Gong,et al.Solution-Processable EpitaxialMetallic Delafossite Oxide Films.Adv.Funct.Mater.2020,30,2002375. Summary of the invention

[0011] Based on the above-mentioned deficiencies in the prior art, the present invention provides a method for preparing a transparent conductive copper chromate epitaxial film with a wide optical band gap, aiming to prepare a transparent conductive CuCrO2 epitaxial film by a simple chemical solution deposition method, and make it have high transmittance in a wide spectral range (including the ultraviolet light region), and at the same time have low resistivity and high carrier mobility at room temperature.

[0012] To achieve the above object, the present invention provides the following technical solutions:

[0013] A method for preparing a wide optical bandgap transparent conductive copper chromate epitaxial film comprises the following steps:

[0014] S1, adding copper nitrate and chromium nitrate into a mixed solvent of ethylene glycol and glacial acetic acid to obtain a precursor colloid;

[0015] S2, using Al2O3 as a growth substrate, after cleaning, forming a film on the surface of the growth substrate by spin coating the precursor colloid, and then pyrolyzing to obtain an amorphous film;

[0016] S3. Post-annealing the amorphous film in a reducing atmosphere to obtain a wide optical bandgap transparent conductive copper chromate epitaxial film.

[0017] The above method successfully prepared copper chromate epitaxial thin films for the first time using chemical solution deposition. Chemical solution deposition is a method of forming a thin film by depositing the precipitate produced by a chemical reaction in the solution on a substrate. This method is relatively simple to operate and does not require complex equipment and processes. By adjusting the process parameters in the preparation process, such as solution concentration, reaction temperature and time, the microstructure of the film, such as grain size, orientation and texture, can be precisely controlled, significantly improving the flatness and density of the film. In addition, the cost of the raw materials and equipment used is low, and the demand for expensive equipment is low, which has significant advantages in controlling costs.

[0018] Furthermore, in step 1, the stoichiometric ratio of copper nitrate to chromium nitrate is 1:1, the volume ratio of ethylene glycol to glacial acetic acid is 1:1-3, and the total molar concentration of each metal element in the precursor colloid is 0.2-0.3 mol / L.

[0019] The above concentrations and ratios directly affect the formation of conductive copper chromate epitaxial film. The reason why the ratio affects the formation of epitaxial film is that, firstly, in terms of chemical reaction balance, the ratio affects the ion concentration, the action of the reducing agent and the pH, thereby changing the reaction direction and the product. Secondly, in terms of crystal growth, the ratio controls the nucleation rate and the supply rate of the deposited atoms, which plays an important role in the uniformity of nucleation and the orderly growth of the film.

[0020] Furthermore, in step 2, the spin coating parameters are set as follows: a rotation speed of 5000-8000 rpm, a spin coating time of 30-40 s, and after the spin coating is completed, the film is placed on a heating plate at a temperature of 150-180° C. for drying for 2-3 min.

[0021] Furthermore, in step 2, the pyrolysis is carried out in an air atmosphere, the pyrolysis temperature is 350-400° C., and the pyrolysis time is 10-15 min.

[0022] Furthermore, in step 3, the annealing is performed in a nitrogen atmosphere with a gas flow rate of 400-500 sccm, an annealing temperature of 650-800° C., and an annealing time of 30-40 min, and the crystal growth is completed through annealing.

[0023] Furthermore, in step 3, the steps of spin coating, pyrolysis and annealing are repeated 20 to 30 times to obtain a crystallized copper chromate epitaxial film.

[0024] This step can regulate the porosity and thickness of the transparent conductive copper chromate epitaxial film. Repeating this step multiple times can create pores between the crystallized film and the spin-coated film, thereby reducing the refractive index of the film, and the thickness of the film can be controlled by the spin-coating speed and the number of spin-coating times. For the copper electrochromate epitaxial film, the higher the transmittance, the higher its application value. According to Fresnel's law, when the thickness and refractive index of the coating satisfy the formula:

[0025] n1d=(2k+1)λ0 / 4, k=0, 1, 2, 3...

[0026] n1=(n0×n s ) 1 / 2

[0027] Among them, n0, n1, n s Represent the refractive index of air, coating and substrate respectively, λ0 and d represent the wavelength of incident light and coating thickness respectively. The transmittance is optimal.

[0028] The refractive index of the Al2O3 substrate is about 1.7, and the refractive index of air is about 1. According to the above formula, when k=0, the best refractive index of the film is calculated to be 1.30. Currently, the bulk material with the lowest refractive index in nature is MgF2, which is 1.38. Therefore, pores need to be introduced to reduce the refractive index of the film and thus increase the transmittance. Taking the incident light wavelength of 600nm as an example, in order to increase the transmittance, the thickness of the film can be calculated to be about 115nm.

[0029] According to the above formula and calculation, the repetition operation and the number of spin coating in this step have an important influence on the light transmittance of the thin film coated on the substrate.

[0030] The present invention also provides a wide optical bandgap transparent conductive copper chromate epitaxial film, the thickness of the copper chromate epitaxial film is 110-130nm, the optical bandgap is 3.10-3.20eV, the room temperature (300K) resistivity is 405.10-415.25mΩcm, and the room temperature carrier mobility is 700.2-750.3cm 2 V -1 s -1 , the carrier concentration at room temperature is 1.9×10 16 ~2.1×10 16 cm -3 .

[0031] The main reasons why it is difficult to synthesize copper chromate epitaxial thin films by chemical deposition are: first, the chemical reaction is complex, there are multiple reactions competing and the redox potential is difficult to control; second, the film formation process is difficult to control, nucleation growth is difficult to control, and stress problems easily lead to film defects; third, the material itself has poor solubility and stability, and is also easy to introduce impurities and defects; fourth, it is limited by process conditions, and temperature, pH value, reaction time and ion concentration are difficult to accurately control. The present invention successfully prepares copper chromate epitaxial thin films by adjusting process details, such as controlling the spin coating speed and time to adjust the thickness of the coating, pyrolysis time, heating temperature, annealing temperature and time, and other conditions, and has excellent performance.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) Simple process: The copper chromate film is prepared by chemical solution deposition method, which has a simple operation process and low demand for expensive equipment, and has significant advantages in controlling costs.

[0034] (2) Lattice epitaxy: For the first time, copper chromate epitaxial thin films were successfully prepared using chemical solution deposition, with excellent crystal growth quality.

[0035] (3) Excellent performance: The room temperature resistivity of the copper chromate epitaxial film prepared by the present invention is 405.10-415.25 mΩcm, and the room temperature carrier mobility is 700.2-750.3 cm 2 V -1 s -1 The optical band gap is about 3.10~3.20eV, and the transmittance at a wavelength of 500nm is greater than 50%, which can meet the needs of transparent conductive applications in the visible and near-infrared bands.

[0036] (4) The present invention provides a method for preparing a wide optical bandgap transparent conductive copper chromate epitaxial film by chemical solution deposition in a non-vacuum environment, which overcomes the difficulties of other preparation methods such as expensive target materials, high equipment investment costs, harsh preparation conditions, and small sample size. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is an XRD photograph of a CuCrO2 epitaxial film deposited on a single crystal Al2O3 substrate in Example 1 of the present invention;

[0038] Figure 2 is a SEM photograph of a CuCrO2 epitaxial film deposited on a single crystal Al2O3 substrate in Example 1 of the present invention;

[0039] Figure 3 is an AFM photograph of a CuCrO2 epitaxial film deposited on a single crystal Al2O3 substrate in Example 1 of the present invention;

[0040] Figure 4 is a TEM photograph of a CuCrO2 epitaxial film deposited on a single crystal Al2O3 substrate in Example 1 of the present invention;

[0041] Figure 5 is an EDS photograph of a CuCrO2 epitaxial film deposited on a single crystal Al2O3 substrate in Example 1 of the present invention;

[0042] Figure 6 is a data curve of resistivity data obtained from a CuCrO2 epitaxial film deposited on a single crystal Al2O3 substrate in Example 1 of the present invention at a temperature range of 100 to 350K;

[0043] Figure 7It is the optical transmittance data curve of the CuCrO2 epitaxial film deposited on the single crystal Al2O3 substrate in the wavelength range of 250-2500nm and the optical band gap fitting curve (inset) in Example 1 of the present invention. DETAILED DESCRIPTION

[0044] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail in combination with the embodiments below. The following content is only an example and explanation of the concept of the present invention. The technicians in the relevant technical field make various modifications or supplements to the specific implementation cases described or replace them with similar methods. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all belong to the protection scope of the present invention.

[0045] The above-mentioned preparation method of the present invention is described below through specific examples and comparative examples.

[0046] Example 1

[0047] This embodiment provides a wide optical bandgap transparent conductive copper chromate epitaxial film and a preparation method thereof.

[0048] The preparation method comprises the following steps:

[0049] S1. According to the molar ratio of Cu element to Cr element of 1:1, copper nitrate and chromium nitrate are mixed in a mixed solvent consisting of ethylene glycol and glacial acetic acid in a volume ratio of 1:1 to obtain a precursor colloid, and the total molar concentration of each metal element in the precursor colloid is 0.2 mol / L.

[0050] S2. Using Al2O3 as the growth substrate, the precursor colloid was spin-coated on the surface of the growth substrate at a spin-coating speed of 5000 rpm and a spin-coating time of 30 seconds. After the spin-coating, the film was placed on a heating plate at a temperature of 150°C for 2 minutes for drying. The dried film was pyrolyzed in an air atmosphere at a pyrolysis temperature of 350°C and a pyrolysis time of 10 minutes.

[0051] S3. After the pyrolysis is completed, annealing is performed in a nitrogen atmosphere with a gas flow rate of 400 sccm, the annealing temperature is 500°C, and the annealing time is 30 minutes. After annealing, the crystal growth is completed. The above spin coating, pyrolysis and annealing steps are repeated 20 times to obtain a crystalline CuCrO2 epitaxial film.

[0052] According to the above method, a wide optical bandgap transparent conductive copper chromate epitaxial film is obtained.

[0053] The thickness of the copper chromate epitaxial film is 120nm, the optical band gap is 3.20eV, the room temperature (300K) resistivity is 413.13mΩcm, and the room temperature carrier mobility is 704.3cm2 V -1 s -1 , the carrier concentration at room temperature is 2.1×10 16 cm -3 .

[0054] Example 2

[0055] This embodiment provides a wide optical bandgap transparent conductive copper chromate epitaxial film and a preparation method thereof.

[0056] The preparation method comprises the following steps:

[0057] S1. According to the molar ratio of Cu element to Cr element of 1:1, copper nitrate and chromium nitrate are mixed in a mixed solvent consisting of ethylene glycol and glacial acetic acid in a volume ratio of 1:3 to obtain a precursor colloid, and the total molar concentration of each metal element in the precursor colloid is 0.3 mol / L.

[0058] S2. Using Al2O3 as the growth substrate, the precursor colloid was spin-coated on the surface of the growth substrate at a spin-coating speed of 8000 rpm and a spin-coating time of 40 seconds. After the spin-coating, the film was placed on a heating plate at a temperature of 180°C for drying for 3 minutes. The dried film was pyrolyzed in an air atmosphere at a pyrolysis temperature of 400°C and a pyrolysis time of 15 minutes.

[0059] S3. After the pyrolysis is completed, annealing is performed in a nitrogen atmosphere with a gas flow rate of 500 sccm, the annealing temperature is 650°C, and the annealing time is 40 minutes. After annealing, the crystal growth is completed. The above spin coating, pyrolysis and annealing steps are repeated 30 times to obtain a crystalline CuCrO2 epitaxial film.

[0060] According to the above method, a wide optical bandgap transparent conductive copper chromate epitaxial film is obtained.

[0061] The thickness of the copper chromate epitaxial film is 118nm, the optical band gap is 3.12eV, the room temperature (300K) resistivity is 410.15mΩcm, and the room temperature carrier mobility is 728.1cm 2 V -1 s -1 , the carrier concentration at room temperature is 2.08×10 16 cm -3 .

[0062] Example 3

[0063] This embodiment provides a wide optical bandgap transparent conductive copper chromate epitaxial film and a preparation method thereof.

[0064] The preparation method comprises the following steps:

[0065] S1. According to the molar ratio of Cu element to Cr element of 1:1, copper nitrate and chromium nitrate are mixed in a mixed solvent consisting of ethylene glycol and glacial acetic acid in a volume ratio of 1:2 to obtain a precursor colloid, and the total molar concentration of each metal element in the precursor colloid is 0.25 mol / L.

[0066] S2. Using Al2O3 as the growth substrate, the precursor colloid was spin-coated on the surface of the growth substrate at a spin-coating speed of 6000 rpm and a spin-coating time of 35 seconds. After the spin-coating, the film was placed on a heating plate at a temperature of 160°C for 2 minutes for drying. The dried film was pyrolyzed in an air atmosphere at a pyrolysis temperature of 360°C and a pyrolysis time of 12 minutes.

[0067] S3. After the pyrolysis is completed, annealing is performed in a nitrogen atmosphere with a gas flow rate of 450 sccm, the annealing temperature is 600°C, and the annealing time is 35 minutes. After annealing, the crystal growth is completed. The above spin coating, pyrolysis and annealing steps are repeated 25 times to obtain a crystalline CuCrO2 epitaxial film.

[0068] According to the above method, a wide optical bandgap transparent conductive CuCrO2 epitaxial film is obtained. The thickness of the copper chromate epitaxial film is 160nm, the optical bandgap is 3.15eV, the room temperature (300K) resistivity is 405.1mΩcm, and the room temperature carrier mobility is 747.9cm 2 V -1 s -1 , the carrier concentration at room temperature is 2.0×10 16 cm -3 .

[0069] Comparative Example 1

[0070] In this comparative example, a CuCrO2 epitaxial thin film was prepared in the same manner as in Example 1, except that the annealing atmosphere used was ethylene glycol and glacial acetic acid in a volume ratio of 1:9.

[0071] After testing, the CuCrO2 epitaxial film prepared in this embodiment is not an epitaxial film. By comparison, it can be seen that the appropriate colloid ratio is conducive to the successful preparation of CuCrO2 epitaxial film.

[0072] Figure 1 This is an XRD photograph of the CuCrO2 epitaxial thin film deposited on the single crystal Al2O3 substrate in Example 1 of the present invention. Figure 1 (a) It can be seen that in addition to the Al2O3 substrate peak, only four diffraction peaks (003), (006), (009), and (0012) appear, indicating that the CuCrO2 film is a c-axis preferentially oriented film. Figure 1(b) The results of the rocking curve test on the (006) peak of CuCrO2 are given. The results show that the half-peak width of the CuCrO2 film (006) is 0.9. The smaller half-peak width value indicates that the c-axis preferred orientation of the CuCrO2 film is better. Figure 1 (c) shows the single crystal φ scan test. It can be seen that the (012) plane of the CuCrO2 film has six φ scan symmetric diffraction peaks arranged at equal intervals of 60°, while the (012) plane of the Al2O3 substrate has three diffraction peaks arranged at equal intervals of 120°, indicating that the CuCrO2 film has six-fold symmetry and that each crystal plane is arranged in order within the plane. The above results indicate that the CuCrO2 film is epitaxially grown on the Al2O3 substrate, and the epitaxial relationship is (001)

[012] CuCrO2‖(001)

[012] Al2O3.

[0073] Figure 2 This is the surface SEM characterization test result of the CuCrO2 epitaxial film deposited on the single crystal Al2O3 substrate in Example 1 of the present invention. From the figure, it can be seen that the surface of the CuCrO2 epitaxial film is very flat and dense, without holes and cracks.

[0074] Figure 3 This is the surface AFM characterization test result of the CuCrO2 epitaxial film deposited on the single crystal Al2O3 substrate in Example 1 of the present invention. From the figure, it can be seen that the surface roughness of the CuCrO2 epitaxial film is about 6.8nm, and the smaller roughness value indicates that the CuCrO2 epitaxial film is relatively flat and smooth.

[0075] Figure 4 This is the TEM characterization test result of the CuCrO2 epitaxial film deposited on the single crystal Al2O3 substrate in Example 1 of the present invention. From the figure, it can be seen that the CuCrO2 epitaxial film shows a clear interface and a layered structure with periodic lattice stripes perpendicular to the c-axis, and there is no dislocation. This crystallographic property is conducive to the in-plane carrier transport of this anisotropic compound. Based on the periodic stripes, the c-axis lattice constant can be determined to be

[0076] Figure 5 This is the surface EDS characterization test result of the CuCrO2 epitaxial film deposited on the single crystal Al2O3 substrate in Example 1 of the present invention. Figure 5 (a) shows the EDS characterization test results of Cu and Cr elements on the surface of CuCrO2 film. It can be seen that Cu and Cr elements are very evenly distributed on the surface of the film. Figure 5 The distribution states of Cu and Cr single elements shown in (b) and (c) indicate that there is no obvious agglomeration of the elements. Figure 5(d) shows the surface element content ratio test results of CuCrO2 film. It can be seen that the content ratio of Cu and Cr elements is about 1:1, which is close to the stoichiometric ratio.

[0077] Figure 6 This is a data curve of resistivity data obtained from the CuCrO2 epitaxial film deposited on the single crystal Al2O3 substrate in Example 1 of the present invention at a temperature range of 100 to 350 K. It can be seen that when the temperature is 300 K, the resistivity of the CuCrO2 epitaxial film is 413.13 mΩcm.

[0078] Figure 7 The optical transmittance data curve of the CuCrO2 epitaxial film deposited on the single crystal Al2O3 substrate in the wavelength range of 250-2500nm and the optical band gap fitting curve (inset) in Example 1 of the present invention are shown in the figure. It can be seen from the figure that the average transmittance of the CuCrO2 epitaxial film in the visible light range reaches 62.71%, and the optical band gap is 3.20eV.

[0079] In summary, the present invention provides a method for preparing a wide optical band gap transparent conductive CuCrO2 epitaxial film by chemical solution deposition in a non-vacuum environment, which overcomes the difficulties of other preparation methods such as expensive target materials, high equipment investment costs, harsh preparation conditions, and small sample size. It has potential application prospects, especially in the preparation of wide optical band gap transparent conductive films and their applications in ultraviolet optoelectronic devices.

[0080] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a wide optical bandgap transparent conductive copper chromate epitaxial film, characterized in that: The following steps are involved: S1, adding copper nitrate and chromium nitrate into a mixed solvent of ethylene glycol and glacial acetic acid to obtain a precursor colloid; S2, using Al2O3 as a growth substrate, after cleaning, forming a film on the surface of the growth substrate by spin coating the precursor colloid, and then pyrolyzing to obtain an amorphous film; S3. Post-annealing the amorphous film in a reducing atmosphere to obtain a wide optical bandgap transparent conductive copper chromate epitaxial film.

2. The method for preparing a wide optical bandgap transparent conductive copper chromate epitaxial film according to claim 1, characterized in that: In step 1, the stoichiometric ratio of copper nitrate to chromium nitrate is 1:1, the volume ratio of ethylene glycol to glacial acetic acid is 1:1-3, and the total molar concentration of each metal element in the precursor colloid is 0.2-0.3 mol / L.

3. The method for preparing a wide optical bandgap transparent conductive copper chromate epitaxial film according to claim 1, characterized in that: In step 2, the spin coating parameters are set as follows: a rotation speed of 5000-8000 rpm, a spin coating time of 30-40 s, and after the spin coating is completed, the film is placed on a heating plate at a temperature of 150-180° C. for drying for 2-3 min.

4. The method for preparing a wide optical bandgap transparent conductive copper chromate epitaxial film according to claim 1, characterized in that: In step 2, the pyrolysis is carried out in an air atmosphere, the pyrolysis temperature is 350-400° C., and the pyrolysis time is 10-15 min.

5. The method for preparing a wide optical bandgap transparent conductive copper chromate epitaxial film according to claim 1, characterized in that: Annealing in step 3 is performed in a nitrogen atmosphere with a gas flow rate of 400-500 sccm, an annealing temperature of 650-800° C., and an annealing time of 30-40 min, and the crystal growth is completed by annealing.

6. The preparation method according to claim 1, characterized in that: In step 3, the steps of spin coating, pyrolysis and annealing are repeated 20 to 30 times to obtain a crystallized copper chromate epitaxial film.

7. A wide optical bandgap transparent conductive copper chromate epitaxial film prepared according to any one of claims 1 to 6, characterized in that: The thickness of the copper chromate epitaxial film is 110-130 nm, the optical band gap is 3.10-3.20 eV, the room temperature (300K) resistivity is 405.10-415.25 mΩcm, and the room temperature carrier mobility is 700.2-750.3 cm 2 V -1 s -1 , the carrier concentration at room temperature is 1.9×10 16 ~2.1×10 16 cm -3 .

Citation Information

Patent Citations

  • Simple chemical preparation method of delafossite structure copper chromium oxide nanocrystalline film

    CN106782876A

  • Preparation method of wide-optical-band-gap transparent conductive lanthanum-doped strontium stannate film

    CN118507145A

  • SOL GEL PROCESS FOR PREPARING Pb(Zr,Ti)O3 THIN FILMS

    WO1990013149A1